Natural co-infection of torque teno virus and porcine circovirus 2 in the reproductive apparatus of swine - Ritterbusch G.A.* (2012)
This work aimed to detect and study natural co-infection of Circoviridae torque teno virus (TTV) and porcine circovirus 2 (PCV2) in the swine reproductive apparatus. Semen and organs from 17 boars were tested by nested and real-time PCR. PCV2 was amplified from semen (47%), lymph nodes (84.6%) and testicles (35.3%). TTV2 was amplified from 16/17 testis and 13/13 lymph nodes. TTV1 DNA was detected in fewer testicle samples (2/17), which were also TTV2 positive. Analyzed ovaries, follicular fluid and uteri of 83 culled sows showed TTV2, TTV1 and PCV2 from 49.3%, 30.1% and 6.0% of the sows, respectively. Sperm analysis indicated insignificant differences between PCV2 and TTVs positive and negative boars. The most frequent pathologic lesion in sows was endometritis (28.9%), but this was unassociated with PCV2 or TTVs detection. These findings question the importance of PCV2 and TTV2 natural co-infection in the pathology of porcine reproductive failures. © 2011 Elsevier Ltd.